2022
DOI: 10.3390/foods11203280
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Streptococcus thermophilus FUA329 Isolated from Human Breast Milk Capable of Producing Urolithin A from Ellagic Acid

Abstract: Urolithin A, a metabolite of ellagic acid, has many beneficial biological activities for people. Strains capable of producing urolithin A from ellagic acid have the hope of becoming the next-generation probiotics. However, only a few species of these strains have been reported. In this study, FUA329, a strain capable of converting ellagic acid to urolithin A in vitro, was isolated from the breast milk of healthy Chinese women. The results of morphological observation, physiological and biochemical tests, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…In a trial conducted in middle-aged and older adults, pomegranate juice consumed daily for 1 year positively impacted cognition . In our previous study, we screened and identified strain S. thermophilus FUA329 capable of transforming EA to UA in vitro . We also elucidated its safety and probiotic properties by conducting acid and bile salt resistance tests in vitro, a drug sensitivity test in a simulated GIT environment in vitro, etc.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a trial conducted in middle-aged and older adults, pomegranate juice consumed daily for 1 year positively impacted cognition . In our previous study, we screened and identified strain S. thermophilus FUA329 capable of transforming EA to UA in vitro . We also elucidated its safety and probiotic properties by conducting acid and bile salt resistance tests in vitro, a drug sensitivity test in a simulated GIT environment in vitro, etc.…”
Section: Discussionmentioning
confidence: 99%
“…38 In our previous study, we screened and identified strain S. thermophilus FUA329 capable of transforming EA to UA in vitro. 18 We also elucidated its safety and probiotic properties by conducting acid and bile salt resistance tests in vitro, a drug sensitivity test in a simulated GIT environment in vitro, etc. We here observed that pomegranate peel itself contained 10 phenolic acids and 16 flavonoids; this result is the same as those of Marra et al 3 Some phenolic acids and flavonoids exhibited a decreasing trend in the unfermented pomegranate peels and peels fermented by S. thermophilus FUA329, especially EA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In studies by Li, F. et al it was found that intestinal microflora metabolite nicotinamide n-oxide promotes mitophagy in microglia, thereby preventing herpes simplex encephalitis [ 170 , 171 ]. In a recent study, it was demonstrated that Streptococcus thermophilus FUA329 can produce urolithins from ellagic acid, which opens the prospect of a new generation of probiotics [ 172 ]. It can be assumed that intestinal dysbacteriosis or sterilization can lead to suppression of the production of mitophagy inducers by the intestinal microbiota, and that was shown in experiments on mice with Ochratoxin A-induced hepatitis.…”
Section: Discussionmentioning
confidence: 99%